Detection of Endosymbiont Candidatus Midichloria mitochondrii and Tickborne Pathogens in Humans Exposed to Tick Bites, Italy - Giovanni Sgroi; Roberta Iatta; Piero Lovreglio; Angela Stufano; Younes Laidoudi; Jairo Alfonso Mendoza-Roldan; Marcos Antonio Bezerra-Santos; Vincenzo Veneziano; Francesco Di Gennaro; Annalisa Saracino; Maria Chironna; Claudio Bandi; et al. (Emerging Infectious Diseases, 2022)
During 2021, we collected blood and serum samples from 135 persons exposed to tick bites in southern Italy. We serologically and molecularly screened for zoonotic tickborne pathogens and only molecularly screened for Candidatus Midichloria mitochondrii. Overall, 62 (45.9%) persons tested positive for tickborne pathogens. Coxiella burnetii was detected most frequently (27.4%), along with Rickettsia spp. (21.5%) and Borrelia spp. (10.4%). We detected Candidatus M. mitochondrii DNA in 46 (34.1%) participants who had statistically significant associations to tickborne pathogens (p<0.0001). Phylogenetic analysis of Candidatus M. mitochondrii sequences revealed 5 clades and 8 human sequence types that correlated with vertebrates, Ixodes spp. ticks, and countries in Europe. These data demonstrated a high circulation of tickborne pathogens and Candidatus M. mitochondrii DNA in persons participating in outdoor activities in southern Italy. Our study shows how coordinated surveillance among patients, clinicians, and veterinarians could inform a One Health approach for monitoring and controlling the circulation of tickborne pathogens.